1984
DOI: 10.1115/1.3239656
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Fan Performance With Inlet Clearance

Abstract: This paper describes a systematic study of the influence of the inlet clearance gap on the performance of a centrifugal fan. Overall fan performance in terms of volume flow rate, pressure rise, stall margin, and efficiency were measured over a range of values of the radial clearance between the impeller and the stationary inlet cone. These data have been correlated as functions of lumped clearance parameters. Additional data on velocity surveys in the impeller discharge are presented and discussed in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…A non-touching seals, such as a labyrinth seal, will reduce the leakage flow rate significantly, compared with the gap that has a direct opening to the fan eye in the current design. The above conclusion agrees with what Wright found on the inlet gap in a scroll cage centrifugal blower (Wright, 1984). …”
Section: Gap Losssupporting
confidence: 82%
See 2 more Smart Citations
“…A non-touching seals, such as a labyrinth seal, will reduce the leakage flow rate significantly, compared with the gap that has a direct opening to the fan eye in the current design. The above conclusion agrees with what Wright found on the inlet gap in a scroll cage centrifugal blower (Wright, 1984). …”
Section: Gap Losssupporting
confidence: 82%
“…The fan shell and the ported diffuser are cut to show the internal structure. Wright (1984) studied the effects of the inlet gap between the fan and the scroll on the fan performance of a scroll cage centrifugal blower. He found that the fan performance increased when the gap size was reduced and the concept of optimum gap size was not valid.…”
Section: Air Entering the Fan Impellermentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of clearance between the impeller and the hub-side wall of the casing to the impeller outer radius s/R 2 is 0.07. The inlet clearance between the impeller and the inlet duct (suction pipe) is 1 mm (20) . The experimental rotational speed of the impeller is 3 000 rpm.…”
Section: Nomenclaturementioning
confidence: 99%
“…The RADFAN procedure was chosen for this investigation because its flexible C-type computational grid topology eases the burden of grid generation for centrifugal geometries and because of the numerical algorithm's proven accuracy and efficiency, in both steady and time-dependent problems [lS, 17, 151. Validation of the RADFAN analysis was accomplished by performing inviscid and viscous simulations of the Row through the Wright radial fan [18,19,201, and comparing the results to experimental data. To assess the ability of RADFAN to predict impeller performance at off-design flow conditions, numerical simulations were performed for the Worthington impeller [21] a t three different operating conditions, and the predicted numerical results were compared with -'…”
mentioning
confidence: 99%